Computational intelligence for managing pandemics - Albuquerque, Victor Hugo C. de; Bhushan, Bharat; Bhushan, Bharat; Hossain Mondal, M. Rubaiyat; Hossain Mondal, Rubaiyat; Khamparia, Aditya; Kumar, Sachin; Podder, Prajoy; Podder, Prajoy (Intelligent Biomedical Data Analysis, 2021)
This book uncovers the stakes and possibilities of handling pandemic diseases with the help of Computational Intelligence, using cases and applications from the current Covid-19 pandemic. The book chapters will focus on the application of CI and its related fields in managing different aspects of Covid-19, including modelling of the disease spread, data-driven prediction, identification of disease hotspots, and medical decision support.